Retention in the Austrian opioid agonist treatment system: a national prospective cohort study - Martin Busch; Charlotte Klein; Alfred Uhl; Hans Haltmayer; Maurice Cabanis; Jean Nicolas Westenberg; Marc Vogel; R. Michael Krausz (BMC, 2021)
Abstract Background Retention in care is a prerequisite for successful recovery, especially for a chronic condition like opioid dependence. Though retention varies greatly depending on the different substitution medication and treatment model, treatment retention is used as an indicator of treatment quality and effectiveness of care on a system and individual level. To monitor the overall quality of the Austrian opioid agonist treatment (OAT) system and to monitor patient satisfaction within the system, a new online-based registry called "eSuchmittel" was introduced in Austria at the beginning of 2011. The objective of this study is to analyze retention rates within the Austrian treatment system and to identify patient characteristics associated with retention, using data collected by the substitution registry. Methods The complete Austrian sample of 4778 registered patients starting treatment between 1.1.2011 to 31.12.2012 were included in the prospective cohort study using data from the Austrian substitution registry. For the statistical analysis, multivariate Cox Regression and Kaplan-Meier survival analysis were used to evaluate retention in treatment. Results The retention rate of the total cohort after two years was around 61%. Retention rates were significantly lower for men (exp(B) = .806, 95% CI 0.714-0.908) and significantly higher for patients aged 30 and older (exp(B) = 1.155, 95% CI 1.044-1.279), among patients located in Vienna (exp(B) = 1.439, 95% CI 1.273-1.626) and among patients prescribed oral slow-release morphine (SROM) (exp(B) = 2.141, 95% CI 1.885-2.430). Conclusions Average retention in the Austrian system is high in comparison to international retention rates. Nationally, SROM demonstrates higher treatment retention when compared to other available substitution medications. Sociodemographic and regional indicators also contribute to higher retention in care. A systematic monitoring of retention rates within a national registry is an important tool helping to evaluate the quality of care. In this study, the Austrian OAT system proves very high retention in care, an important success criterion.